Spin-phonon interaction in nanocrystalline Dy3Fe5O12 probed by Raman spectroscopy: Effects of magnetic ordering - Bojan Stojadinović; Zorana Dohčević-Mitrović; Sonja Aškrabić; Novica Paunović; M.T. Rahul; B. Raneesh; Nandakumar Kalarikkal (Journal of Science: Advanced Materials and Devices, 2023)
We report the effects of magnetic ordering on the temperature evolution of the Raman modes in nanocrystalline Dy3Fe5O12. The Dy3Fe5O12 was synthesized by an aqueous sol–gel method. X-ray diffraction, Raman spectroscopy and transmission electron microscopy studies revealed the phase purity and nanocrystalline nature. We particularly focused on the spin-phonon coupling mechanism in Dy3Fe5O12, as this interaction can greatly affect the magnetoelectric and multiferroic properties of Dy3Fe5O12. Below TC, four phonon modes from the middle- and high-frequency regions displayed anomalous behavior, which was ascribed to the spin-phonon interaction. The application of the mean-field approach enabled us to quantify the spin-phonon coupling strength for each of these phonon modes. Our study has shown that different phonon modes are coupled to ferromagnetic or antiferromagnetic ordering depending on the type of vibrational motion characteristic for a specific mode. These results significantly enhance the understanding of the complex spin-phonon coupling mechanism and its implications on the multifaceted properties of nanocrystalline Dy3Fe5O12, such as multiferroic, magnetoelectric, and magnetocaloric properties. Moreover, these findings have the potential to drive advancements in the optimization and development of spintronic devices.